ULAMA BERBAGI OTORITAS: Fungsi dan Peran MUI Kota Padangsidimpuan dalam meningkatkan kesadaran dan budaya hukum masyarakat - Ahmatnijar, Ahmatnijar (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
The authority of MUI Padangsidimpuan in function theoretically is as container deliberation, silaturrahmi the scholars, zuama and Muslim scholars in protecting the people, develop and practice the teachings of Islam, raising ukhuwah Islamiyah in Islamic life. As a container representing Muslims in the relationship and inter-religious consultations and giving fatwas to the Muslims and the government, whether requested or not requested. The authority of MUI Padangsidimpuan to deal with globalization, liberalization, institutions that have authority, other Islamic religious social organization. For that function should be developed according to the quality and quantity of life issues are growing. While the role of the authorities practically have shared with agencies that have the authority and the authority that created pure, so the authority was scattered and terfungsikan by other agencies